Preparation method for controllably preparing two-dimensional high-entropy sulfide efficient electrolyzed water catalyst based on two-dimensional high-entropy hydroxide template
Through the low-temperature vulcanization method based on the two-dimensional high-entropy hydroxide template, the harsh conditions of high-temperature and high pressure in the synthesis of two-dimensional high-entropy sulfides in the prior art are solved, and high-efficiency and universal large-throughput preparation of high-performance two-dimensional high-entropy sulfides are achieved, with excellent conductivity and stability.
Patent Information
- Application Number
- CN202411654094.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing direct vulcanization method requires harsh conditions such as high temperature and high pressure during the production of two-dimensional high entropy sulfides, resulting in uneven reactions, impure products, uneven element distribution, and phase/structure separation.
The low-temperature vulcanization method based on two-dimensional high-entropy hydroxide template is adopted. By performing vulcanization at low temperature, the phase/structure separation problems caused by high-temperature vulcanization are avoided, and the uniform mixing and regulation of different elements are achieved.
The synthesis temperature of two-dimensional high-entropy sulfides was successfully reduced, the problems caused by high-temperature vulcanization were avoided, and high-efficiency and universal large-throughput preparation of high-performance two-dimensional high-entropy sulfides were achieved, with excellent conductivity and stability.
Smart Images

Figure HDA0005141709950000011 
Figure HDA0005141709950000012 
Figure HDA0005141709950000013
Abstract
Description
1. Technical field:
[0001] The present invention relates to a high-throughput, universal, low-cost controllable low-temperature synthesis technology for preparing a two-dimensional high-entropy sulfide water electrolysis catalyst, belonging to the technical field of controllable preparation of high-entropy nanomaterials and water electrolysis catalysts, and specifically to a method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template. 2. Background technology:
[0002] The excessive consumption of non-renewable fossil fuels has exacerbated the global energy and environmental crisis, leading to an urgent need to develop clean, efficient and sustainable energy conversion technologies. Hydrogen production by water electrolysis is a clean, efficient, green and large-scale energy conversion process. Theoretically, the water decomposition voltage is 1.23V, but in fact, the industrial water decomposition voltage is 1.8V~2.0V. This is precisely due to the existence of the water dissociation energy barrier, which leads to the overpotential (actual water electrolysis voltage-theoretical water electrolysis voltage). Overpotential will cause more resources to be consumed in the water decomposition process, causing the cost of hydrogen production to rise rapidly. Therefore, there is an urgent need to develop a low-cost, low-overpotential, high-performance water electrolysis catalyst to realize the industrialization of water electrolysis hydrogen production.
[0003] Two-dimensional high-entropy sulfides are two-dimensional nanomaterial systems composed of five or more elements in approximately equiatomic proportions. Their structure has ultra-thin two-dimensional planar characteristics, which makes the material have highly exposed surface active sites. In terms of composition, the mixture of multiple elements brings rich surface chemical properties and diverse electronic structures. The presence of multiple elements provides a large number of surface active sites, which makes two-dimensional high-entropy sulfides have higher activity and selectivity in catalytic reactions. For example: in the electrocatalytic hydrogen evolution reaction (HER), it can show excellent catalytic performance, reduce the reaction overpotential, and increase the reaction rate; and the synergistic effect between different elements can optimize the electronic structure and physicochemical properties of the material, so that it can show better performance than single-component materials in fields such as energy storage and catalysis; by changing the type and proportion of elements, the performance of two-dimensional high-entropy sulfides can be precisely controlled to meet the needs of different application scenarios, and the complex configuration brought by the high-entropy structure and the interaction between multiple elements make the material generally perform well in thermal and chemical stability, and can maintain the stability of structure and performance under harsh environmental conditions. However, due to the high sulfurization temperature of sulfides and the easy phase / structural segregation of materials at high temperatures, the synthesis of two-dimensional high-entropy sulfides faces major challenges. To achieve uniform mixing of different elements and to regulate their ultra-thin thickness, it is necessary to accurately control temperature, pressure and energy field to achieve the required performance in terms of size, phase, shape, cross-section and surface decoration. Two-dimensional high-entropy sulfides have both rich surface chemical properties and ultra-high conductivity, making them an essential core material for promoting the development of efficient water electrolysis catalysts.
[0004] With the continuous in-depth study of two-dimensional high-entropy sulfide materials, various preparation methods have been reported one after another. Common high-entropy alloy synthesis methods such as thermal shock method, solvothermal method, cation exchange method, etc. all have their own advantages and disadvantages and applicable scope, and require precise control of reaction parameters (such as temperature, pressure, reaction time, solvent selection, etc.). At the same time, the synthesis process may face problems such as uneven reaction, impure products, and uneven element distribution. Among them, the direct sulfurization method has attracted wide research attention due to its simple operation. However, the synthesis conditions required for this method are relatively harsh, requiring a high temperature / high pressure synthesis environment, and phase / structure separation is prone to occur during the preparation process. Therefore, the large-throughput controllable preparation of two-dimensional high-entropy sulfides faces huge challenges. In-situ sulfurization using two-dimensional high-entropy hydroxides as templates will effectively avoid problems such as phase / structure separation caused by high-temperature sulfurization, and further reduce the temperature required for sulfurization, and efficiently synthesize high-performance two-dimensional high-entropy sulfides with large throughput. 3. Summary of the invention:
[0005] The technical problem to be solved by the present invention is: in view of the harsh reaction conditions such as high temperature and high pressure required in the process of producing two-dimensional high-entropy sulfides by the existing direct sulfurization method, the phase / structure separation caused by uneven reaction, impure products, and uneven element distribution. In order to reduce the difficulty of synthesizing two-dimensional high-entropy sulfides and controllably prepare large-flux two-dimensional high-entropy sulfides, the present invention provides a preparation method for a two-dimensional high-entropy sulfide efficient electrolytic water catalyst that can be controlled based on a two-dimensional high-entropy hydroxide template. The two-dimensional high-entropy sulfide efficient electrolytic water catalyst is prepared by using the technical solution of the present invention, which can effectively reduce the temperature of sulfurization and avoid phase / structure separation. The technical solution of the present invention, in the first step of the synthesis of high-entropy hydroxide, adds stirring, which can effectively avoid phase separation of different metal elements and promote the effective combination of different elements; then, the synthesized high-entropy hydroxide is used as a template, and further in-situ sulfurization is performed to form a two-dimensional high-entropy sulfide, thereby improving the conductivity and stability of the material.
[0006] In order to solve the above problems, the technical solution adopted by the present invention is:
[0007] The present invention provides a method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst in a controllable manner based on a two-dimensional high-entropy hydroxide template, the preparation method comprising the following steps:
[0008] a. adding at least five metal precursors, ammonium fluoride and urea into a polytetrafluoroethylene liner, and adding deionized water to form a precursor solution;
[0009] b. Ultrasonic mixing the precursor solution obtained in step a is uniformly carried out, and the mixture is transferred to a reaction vessel;
[0010] c. Then, the reaction kettle is placed in an oil bath for stirring, reacting at 100-200° C., and the product after the reaction is washed and dried to obtain a two-dimensional high entropy hydroxide;
[0011] d. Take 10-100 mg of the two-dimensional high entropy hydroxide obtained in step c and place it in the middle of a single-temperature zone tubular furnace, and place a crucible filled with sulfur powder at the front air inlet of the tubular furnace, wherein the mass ratio of the added sulfur powder to the taken two-dimensional high entropy hydroxide is 5-20:1;
[0012] e. Remove impurity gases from the atmosphere of the quartz tube in the tube furnace, introduce argon gas with a purity of 99.999% at a flow rate of 300 to 600 sccm, remove other gases in the quartz tube, and introduce the gas for 10 to 20 minutes; during the reaction, continuously introduce inert argon gas as a protective gas;
[0013] f. When the temperature of the tube furnace rises to 300-400°C, push the sulfur powder in the crucible into the furnace and keep the temperature constant for 30-60 minutes;
[0014] g. The argon gas described in step e is continuously introduced until the temperature drops to room temperature. After the reaction is completed, the argon gas is turned off to obtain a two-dimensional high entropy sulfide product.
[0015] According to the above-mentioned preparation method of controllable preparation of two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on two-dimensional high-entropy hydroxide template, the at least five metal precursors described in step a are based on four metal salts of FeCl2·4H2O, NiCl2, RuCl3 and MoCl5, and then at least one of TaCl5, MnCl2·4H2O, CoCl2, CuCl2, NbCl5, ZnCl2, WCl6, VCl3, Rh(NO3)3, H2PtCl6·6H2O, IrCl3, PdCl2, GrCl3·6H2O, AgNO3, SnCl2·2H2O, SbCl3 and ReCl3 is added; the total amount of all metal precursor substances added in step a is 0.05~0.15mmol, and the amount of substances between each metal precursor is the same.
[0016] According to the above-mentioned method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst that can be controlled based on a two-dimensional high-entropy hydroxide template, the molar ratio of the total amount of all metal precursors, ammonium fluoride and urea added in step a is 1:1~4:1~8.
[0017] According to the above-mentioned method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template, the added mass ratio between the total amount of all metal precursors, ammonium fluoride and urea and deionized water in step a is 1:20-100.
[0018] According to the above-mentioned method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst that can be controlled based on a two-dimensional high-entropy hydroxide template, the ultrasonic time in step b is 5 to 15 minutes.
[0019] According to the above-mentioned method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst that can be controlled based on a two-dimensional high-entropy hydroxide template, the rotation speed during stirring in step c is 400-600 r / min, and the reaction time is 2-10 h.
[0020] According to the above-mentioned method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template, the length of the crucible in step d is 10 to 15 cm, and the length from the crucible to the constant temperature zone of the tubular furnace is 20 to 25 cm.
[0021] According to the above-mentioned method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst that can be controlled based on a two-dimensional high-entropy hydroxide template, the flow rate of argon gas during the reaction process in step e is 50 to 200 sccm.
[0022] According to the above-mentioned method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst that can be controlled based on a two-dimensional high-entropy hydroxide template, the heating rate of the tubular furnace temperature in step f is 1 to 10°C / min.
[0023] From the above, it can be seen that the technical solution of the present invention is as follows: the first step is to use low-temperature technology to assist in the synthesis of two-dimensional high-entropy hydroxides to ensure the effective formation of high-entropy structures; the second step is to use two-dimensional high-entropy hydroxides as templates to perform in-situ low-temperature sulfurization to effectively scale up and universally prepare two-dimensional high-entropy sulfides (i.e., by controlling the sulfurization temperature, sulfur powder mass and reaction time, the two-dimensional high-entropy hydroxides are sulfurized to effectively synthesize two-dimensional high-entropy sulfides with stable structures and high conductivity).
[0024] The positive beneficial effects of the present invention are:
[0025] 1. The technical solution of the present invention utilizes a two-dimensional high-entropy hydroxide template and is synthesized through low-temperature technology, which solves the problems of phase separation and segregation of different metal elements in the current two-dimensional high-entropy materials, and promotes the effective combination of different elements in the high-entropy structure; and uses this as a template for in-situ sulfurization, and has successfully prepared 29 two-dimensional high-entropy sulfides, proving that this method can achieve the universal preparation of two-dimensional high-entropy materials.
[0026] 2. Compared with the prior art, the technical solution of the present invention utilizes two-dimensional high-entropy hydroxide as a template and then performs in-situ sulfurization treatment, which can reduce the temperature required for the synthesis of two-dimensional high-entropy sulfides. The current sulfurization temperature used is lower than 400°C, avoiding the technical limitations of high temperature and high pressure required for the synthesis of two-dimensional high-entropy sulfides; at the same time, it effectively avoids problems such as phase / structure separation caused by high-temperature sulfurization.
[0027] 3. The preparation method of the present invention requires a low temperature during the reaction process, which can effectively reduce the difficulty of synthesis. Moreover, the method has low requirements for equipment conditions, simple operation procedures and processes, and can be completed in only two steps, which can effectively reduce the production process and energy consumption, and can universally and scalably prepare a series of high-performance two-dimensional high-entropy hydroxides and two-dimensional high-entropy sulfides in large quantities. Therefore, the method of the present invention can be used as an ideal method for the industrial production of two-dimensional high-entropy high-entropy hydroxides and two-dimensional high-entropy sulfides. 4. Description of the drawings:
[0028] Figure 1 The present invention is a schematic diagram of a preparation device for controllably preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template; the controllable preparation of two-dimensional high-entropy sulfide is achieved by using two-dimensional high-entropy hydroxide as a template.
[0029] Figure 2 The present invention implements all embodiments of the controllable preparation of two-dimensional high-entropy sulfide efficient water electrolysis catalysts based on a two-dimensional high-entropy hydroxide template; that is, a series of two-dimensional high-entropy sulfides prepared by the method of the present invention, including 17 five-element two-dimensional high-entropy sulfides, 8 six-element two-dimensional high-entropy sulfides, 3 seven-element two-dimensional high-entropy sulfides, and 1 eight-element two-dimensional high-entropy sulfide.
[0030] Figure 3 SEM image of the quinary FeNiRuMoPt-S prepared in Example 1 of the present invention;
[0031] Depend on Figure 3 It can be seen that the prepared five-element two-dimensional high-entropy sulfide shows a two-dimensional nanoflower structure.
[0032] Figure 4 EDS Mapping of the quinary FeNiRuMoPt-S prepared in Example 1 of the present invention;
[0033] Depend on Figure 4 It can be seen that Fe, Ni, Ru, Mo, Pt and S in the prepared quinary FeNiRuMoPt-S successfully formed a solid solution phase structure without element separation.
[0034] Figure 5 LSV diagram of hydrogen evolution performance of quinary FeNiRuMoPt-S prepared in Example 1 of the present invention;
[0035] Depend on Figure 5 It can be seen that FeNiRuMoPt-S has excellent hydrogen evolution performance at 10 mA / cm -2 The overpotential is only 50mV.
[0036] Figure 6LSV diagram of oxygen evolution performance of quinary FeNiRuMoPt-S prepared in Example 1 of the present invention;
[0037] Depend on Figure 6 It can be seen that FeNiRuMoPt-S has excellent oxygen evolution performance at 10 mA / cm -2 The overpotential is only 235mV.
[0038] Figure 7 SEM image of hexavalent FeNiRuMoCoW-S prepared in Example 2 of the present invention;
[0039] Depend on Figure 7 It can be seen that the prepared six-membered two-dimensional high-entropy sulfide shows a two-dimensional nanoflower structure.
[0040] Figure 8 EDS Mapping of the hexavalent FeNiRuMoCoW-S prepared in Example 2 of the present invention;
[0041] Depend on Figure 8 It can be seen that Fe, Ni, Ru, Mo, Co, W and S in the prepared hexameric FeNiRuMoCoW-S successfully form a solid solution phase structure without element separation.
[0042] Fig. 9 LSV diagram of hydrogen evolution performance of hexavalent FeNiRuMoCoW-S prepared in Example 2 of the present invention;
[0043] Depend on Fig. 9 It can be seen that FeNiRuMoCoW-S has excellent hydrogen evolution performance at 10 mA / cm -2 The overpotential is only 196mV.
[0044] Fig.10 LSV diagram of oxygen evolution performance of hexavalent FeNiRuMoCoW-S prepared in Example 2 of the present invention;
[0045] Depend on Fig.10 It can be seen that FeNiRuMoCoW-S has excellent oxygen evolution performance at 10mA / cm -2 The overpotential is only 95mV.
[0046] Fig.11 SEM image of the seven-membered FeNiRuMoCoVZn-S prepared in Example 3 of the present invention;
[0047] Depend on Fig.11 It can be seen that the prepared seven-membered two-dimensional high-entropy sulfide shows a two-dimensional nanoflower structure.
[0048] Fig.12EDS Mapping of the seven-membered FeNiRuMoCoVZn-S prepared in Example 3 of the present invention;
[0049] Depend on Fig.12 It can be seen that Fe, Ni, Ru, Mo, Co, V, Zn and S in the prepared seven-membered FeNiRuMoCoVZn-S successfully formed a solid solution phase structure without element separation.
[0050] Fig.13 LSV diagram of hydrogen evolution performance of the seven-membered FeNiRuMoCoVZn-S prepared in Example 3 of the present invention;
[0051] Depend on Fig.13 It can be seen that FeNiRuMoCoVZn-S has excellent hydrogen evolution performance at 10 mA / cm -2 The overpotential is only 173mV.
[0052] Fig.14 LSV diagram of oxygen evolution performance of the seven-membered FeNiRuMoCoVZn-S prepared in Example 3 of the present invention;
[0053] Depend on Fig.14 It can be seen that the seven-element FeNiRuMoCoVZn-S has excellent oxygen evolution performance at 10 mA / cm -2 The overpotential is only 213mV.
[0054] Fig.15 SEM image of the octal FeNiRuMoCoVWZn-S prepared in Example 4 of the present invention;
[0055] Depend on Fig.15 It can be seen that the prepared octane-two-dimensional high-entropy sulfide shows a two-dimensional nanoflower structure.
[0056] Fig.16 EDS Mapping of the octal FeNiRuMoCoVWZn-S prepared in Example 4 of the present invention;
[0057] Depend on Fig.16 It can be seen that Fe, Ni, Ru, Mo, Co, V, W, Zn and S in the prepared octal FeNiRuMoCoVWZn-S successfully formed a solid solution phase structure without element separation.
[0058] Fig.17 LSV diagram of hydrogen evolution performance of octal FeNiRuMoCoVWZn-S prepared in Example 4 of the present invention;
[0059] Depend on Fig.17 It can be seen that FeNiRuMoCoVWZn-S has excellent hydrogen evolution performance at 10 mA / cm-2 The overpotential is only 235mV.
[0060] Fig.18 LSV diagram of oxygen evolution performance of octal FeNiRuMoCoVWZn-S prepared in Example 4 of the present invention;
[0061] Depend on Fig.18 It can be seen that FeNiRuMoCoVWZn-S has excellent oxygen evolution performance at 10 mA / cm -2 The overpotential is only 280mV. V. Specific implementation methods:
[0062] The present invention is further described below in conjunction with embodiments, but the protection scope of the technical solution of the present invention is not limited thereto.
[0063] Embodiment 1:
[0064] The present invention provides a method for efficiently synthesizing five-membered FeNiRuMoPt-S based on five-membered FeNiRuMoPt-OH as a template, and the detailed steps are as follows:
[0065] a. Put 19.88 mg of FeCl2·4H2O, 13.25 mg of NiCl2, 20.85 mg of RuCl3, 27.30 mg of MoCl5 and 25.92 mg of H2PtCl6·6H2O powder into a 50 mL polytetrafluoroethylene liner, then add 151.67 mg of urea, 37.04 mg of ammonium fluoride, and then add 30 mL of deionized water to prepare a precursor solution;
[0066] b. Ultrasonicate the precursor solution obtained in step a for 10 min to mix evenly, and then transfer it to a reactor;
[0067] c. Then, the reactor was placed in an oil bath for stirring. During the reaction, the stirring speed was controlled to be 477 r / min, the reaction temperature was 150° C., and the reaction time was 6 h. After the reaction, the reactor was frozen and dried in sequence to obtain the five-element FeNiRuMoPt-OH.
[0068] d. Take 15 mg of the five-element FeNiRuMoPt-OH obtained after drying in step c and place it in the middle of a single-temperature zone tubular furnace. Place two crucibles filled with sulfur powder at the front air inlet of the tubular furnace. The amount of sulfur powder added to the two crucibles is 640 mg. The length of the two crucibles is 10 cm, and the length from the crucible to the temperature zone is 25 cm.
[0069] e. Remove impurity gases from the atmosphere of the quartz tube in the tube furnace, introduce argon gas with a purity of 99.999% at a flow rate of 300 sccm, remove other gases in the quartz tube, and the introduction time is 10 min; continue to introduce argon gas as a protective gas during the reaction process; the introduction flow rate of argon gas as a reaction protective gas in step e is 100 sccm;
[0070] f. When the temperature of the tube furnace rises to 350°C (the heating rate is controlled to be 5°C / min during the heating process of the tube furnace), push the sulfur powder in the first crucible and keep the temperature constant for 30 minutes; then push the sulfur powder in the second crucible and keep the temperature constant for 30 minutes;
[0071] g. After the reaction is completed, the argon gas described in step e is continuously introduced until the temperature drops to room temperature, and the argon gas is turned off to obtain the product five-element FeNiRuMoPt-S.
[0072] Embodiment 2:
[0073] The present invention provides a method for efficiently synthesizing hexavalent FeNiRuMoCoW-S based on hexavalent FeNiRuMoCoW-OH as a template, and the detailed steps are as follows:
[0074] a. Put 19.88 mg of FeCl2·4H2O, 13.25 mg of NiCl2, 20.85 mg of RuCl3, 27.30 mg of MoCl5, 13.25 mg of CoCl2 and 40.05 mg of WCl6 powder into a 50 mL polytetrafluoroethylene liner, then add 151.67 mg of urea, 37.04 mg of ammonium fluoride, and then add 30 mL of deionized water to make a precursor solution;
[0075] b. Ultrasonicate the precursor solution obtained in step a for 10 minutes to mix evenly, and then put it into a reactor;
[0076] c. Then, the reactor was placed in an oil bath for stirring. During the reaction, the stirring speed was 477 r / min, the reaction temperature was 150° C., and the reaction time was 6 h. After the reaction, the mixture was frozen and dried in sequence to obtain hexavalent FeNiRuMoCoW-OH.
[0077] d. Take 15 mg of the dried hexavalent FeNiRuMoCoW-OH in step c and place it in the middle of a single-temperature zone tubular furnace. Place two crucibles filled with sulfur powder at the front air inlet of the tubular furnace. The amount of sulfur powder added to the two crucibles is 640 mg. The length of the two crucibles is 10 cm, and the length from the crucible to the temperature zone is 25 cm.
[0078] e. Remove impurity gases from the atmosphere of the quartz tube in the tube furnace, introduce argon gas with a purity of 99.999% at a flow rate of 300 sccm, remove other gases in the quartz tube, and the introduction time is 10 min; continue to introduce argon gas as a protective gas during the reaction process; the introduction flow rate of argon gas as a reaction protective gas in step e is 100 sccm;
[0079] f. When the temperature of the tube furnace rises to 350°C (the heating rate of the tube furnace is 5°C / min), push the sulfur powder in the first crucible and keep the temperature constant for 30 minutes; then push the sulfur powder in the second crucible and keep the temperature constant for 30 minutes;
[0080] g. After the reaction is completed, the argon gas described in step e is continuously introduced until the temperature drops to room temperature, and the argon gas is turned off to obtain the product hexavalent FeNiRuMoCoW-S.
[0081] Embodiment 3:
[0082] The present invention provides a method for efficiently synthesizing seven-membered FeNiRuMoCoVZn-S based on seven-membered FeNiRuMoCoVZn-OH as a template, and the detailed steps are as follows:
[0083] a. Put 19.88 mg of FeCl2·4H2O, 13.25 mg of NiCl2, 20.85 mg of RuCl3, 27.30 mg of MoCl5, 13.25 mg of CoCl2, 16.2 mg of VCl3 and 13.64 mg of ZnCl2 powder into a 50 mL polytetrafluoroethylene liner, then add 151.67 mg of urea, 37.04 mg of ammonium fluoride, and then add 30 mL of deionized water to make a precursor solution;
[0084] b. Ultrasonicate the precursor solution obtained in step a for 10 minutes to mix evenly, and then put it into a reactor;
[0085] c. Then, the reactor was placed in an oil bath for stirring. During the reaction, the stirring speed was 477 r / min, the reaction temperature was 150° C., and the reaction time was 6 h. After the reaction, the reactor was frozen and dried in sequence to obtain the seven-membered FeNiRuMoCoVZn-OH.
[0086] d. Take 15 mg of the seven-membered FeNiRuMoCoVZn-OH dried in step c and place it in the middle of a single-temperature zone tubular furnace. Place two crucibles filled with sulfur powder at the front air inlet of the tubular furnace. The amount of sulfur powder added to the two crucibles is 640 mg. The length of the two crucibles is 10 cm, and the length from the crucible to the temperature zone is 25 cm.
[0087] e. Remove impurity gases from the atmosphere of the quartz tube in the tube furnace, introduce argon gas with a purity of 99.999% at a flow rate of 300 sccm, remove other gases in the quartz tube, and the introduction time is 10 min; continue to introduce argon gas as a protective gas during the reaction process; the introduction flow rate of argon gas as a reaction protective gas in step e is 100 sccm;
[0088] f. When the temperature of the tube furnace rises to 350°C (the heating rate is 5°C / min during the heating process of the tube furnace), push the sulfur powder in the first crucible and keep the temperature constant for 30 minutes; then push the sulfur powder in the second crucible and keep the temperature constant for 30 minutes;
[0089] g. After the reaction is completed, the argon gas described in step e is continuously introduced until the temperature drops to room temperature, and the argon gas is turned off to obtain the product seven-membered FeNiRuMoCoVZn-S.
[0090] Embodiment 4:
[0091] The present invention provides a method for efficiently synthesizing octa-FeNiRuMoCoVWZn-S based on octa-FeNiRuMoCoVWZn-OH as a template, and the detailed steps are as follows:
[0092] a. Put 19.88 mg of FeCl2·4H2O, 13.25 mg of NiCl2, 20.85 mg of RuCl3, 27.30 mg of MoCl5, 13.25 mg of CoCl2, 16.2 mg of VCl3, 13.64 mg of ZnCl2 and 40.05 mg of WCl6 powder into a 50 mL polytetrafluoroethylene liner, then add 151.67 mg of urea, 37.04 mg of ammonium fluoride, and then add 30 mL of deionized water to prepare a precursor solution;
[0093] b. Ultrasonicate the precursor solution obtained in step a for 10 minutes to mix evenly, and then put it into a reactor;
[0094] c. Then, the reactor was placed in an oil bath for stirring. During the reaction, the stirring speed was 477 r / min, the reaction temperature was 150° C., and the reaction time was 6 h. After the reaction was completed, the reaction was sequentially frozen and dried to obtain the octal FeNiRuMoCoVWZn-OH.
[0095] d. Take 15 mg of the octal FeNiRuMoCoVWZn-OH dried in step c and place it in the middle of a single-temperature zone tubular furnace. Place two crucibles filled with sulfur powder at the front air inlet of the tubular furnace. The amount of sulfur powder added to the two crucibles is 640 mg. The length of the two crucibles is 10 cm, and the length from the crucible to the temperature zone is 25 cm.
[0096] e. Remove impurity gases from the atmosphere of the quartz tube in the tube furnace, introduce argon gas with a purity of 99.999% at a flow rate of 300 sccm, remove other gases in the quartz tube, and the introduction time is 10 min; continue to introduce argon gas as a protective gas during the reaction process; the introduction flow rate of argon gas as a reaction protective gas in step e is 100 sccm;
[0097] f. When the temperature of the tube furnace rises to 350°C (the heating rate is 5°C / min during the heating process of the tube furnace), push the sulfur powder in the first crucible and keep the temperature constant for 30 minutes; then push the sulfur powder in the second crucible and keep the temperature constant for 30 minutes;
[0098] g. After the reaction is completed, the argon gas described in step e is continuously introduced until the temperature drops to room temperature, and the argon gas is turned off to obtain the product octa-element FeNiRuMoCoVWZn-S.
Claims
1. A method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template, characterized in that: The preparation method comprises the following steps: a. adding at least five metal precursors, ammonium fluoride and urea into a polytetrafluoroethylene liner, and adding deionized water to form a precursor solution; b. Ultrasonic mixing the precursor solution obtained in step a is uniformly carried out, and the mixture is transferred to a reaction vessel; c. Then, the reaction kettle is placed in an oil bath for stirring, reacting at 100-200° C., and the product after the reaction is washed and dried to obtain a two-dimensional high entropy hydroxide; d. Take 10-100 mg of the two-dimensional high entropy hydroxide obtained in step c and place it in the middle of a single-temperature zone tubular furnace, and place a crucible filled with sulfur powder at the front air inlet of the tubular furnace, wherein the mass ratio of the added sulfur powder to the taken two-dimensional high entropy hydroxide is 5-20:1; e. Remove impurity gases from the atmosphere of the quartz tube in the tube furnace, introduce argon gas with a purity of 99.999% at a flow rate of 300 to 600 sccm, remove other gases in the quartz tube, and introduce the gas for 10 to 20 minutes; during the reaction, continuously introduce inert argon gas as a protective gas; f. When the temperature of the tube furnace rises to 300-400°C, push the sulfur powder in the crucible into the furnace and keep the temperature constant for 30-60 minutes; g. The argon gas described in step e is continuously introduced until the temperature drops to room temperature. After the reaction is completed, the argon gas is turned off to obtain a two-dimensional high entropy sulfide product.
2. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template according to claim 1, characterized in that: The at least five metal precursors described in step a are based on four metal salts of FeCl2·4H2O, NiCl2, RuCl3 and MoCl5, and at least one of TaCl5, MnCl2·4H2O, CoCl2, CuCl2, NbCl5, ZnCl2, WCl6, VCl3, Rh(NO3)3, H2PtCl6·6H2O, IrCl3, PdCl2, GrCl3·6H2O, AgNO3, SnCl2·2H2O, SbCl3 and ReCl3 is added; the total amount of all metal precursor substances added in step a is 0.05~0.15mmol, and the amount of substances between each metal precursor is the same.
3. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template according to claim 1, characterized in that: In step a, the molar ratio of the total amount of all metal precursors, ammonium fluoride and urea added is 1:1-4:1-8.
4. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template according to claim 1, characterized in that: In step a, the mass ratio of the total amount of all metal precursors, ammonium fluoride and urea to deionized water is 1:20-100.
5. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template according to claim 1, characterized in that: The ultrasonic time in step b is 5 to 15 minutes.
6. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template in a controllable manner according to claim 1, characterized in that: The stirring speed in step c is 400-600 r / min, and the reaction time is 2-10 h.
7. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template according to claim 1, characterized in that: The length of the crucible in step d is 10 to 15 cm, and the length from the crucible to the constant temperature zone of the tubular furnace is 20 to 25 cm.
8. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template in a controllable manner according to claim 1, characterized in that: The flow rate of argon gas during the reaction in step e is 50-200 sccm.
9. The method for preparing a two-dimensional high-entropy sulfide efficient water electrolysis catalyst based on a two-dimensional high-entropy hydroxide template in a controllable manner according to claim 1, characterized in that: The heating rate of the tube furnace temperature in step f is 1 to 10° C. / min.
Citation Information
Patent Citations
Preparation method and application of nano high-entropy alloy difunctional electrocatalyst
CN117187860A
Cited By
High-entropy trans-perovskite catalyst and preparation method and application thereof
CN120818842A
Hollow high-entropy transition metal hydroxide crystal and preparation method thereof
CN121451275A